Effectiveness of Lidocaine Cream for Reducing Pain Sensation of Pre Injection of Subcutaneous Lidocaine in Lumbal Puncture Diagnostic and Therapeutic Procedures - Theresia Christin; Andika Oktaparasta; Ratri Wulandari Sulasiningrum (Jurnal Kedokteran dan Kesehatan : Publikasi Ilmiah Fakultas Kedokteran Universitas Sriwijaya, 2020)
Lumbar puncture is one of the methods that is quite often performed for various purposes. There is no global agreement regarding the use of local anesthesia in subcutaneous or topical infiltration prior to LP. Topical anesthesia injection in lumbar puncture still cause pain, there should be needing additional topical anesthesia. The aim of the study is comparing the effectiveness between lidocaine cream and placebo cream prior lidocaine subcutaneous injection to reduce pain sensation in LP procedures. The study was conducted in July-October 2019, randomized and clinical trial (RCT) by sampling technique using block randomization method. Sample was divided into two group. Pain scale was assessed when the needle touched the skin, subcutaneously and overall in both groups. Data analysis using SPSS ver 22 for windows. The average age of subjects is 38.50±14.43 years and majority are women (57.9%). There is significance difference of pain scale between groups when needle touched the skin (p=0,035), meanwhile, there is not significance difference when needle subcutaneously (p=0,061) and overall (p=0,182) in both groups. Lidocaine cream has been shown to be significantly more effective in reducing pain pre lidocaine subcutaneous injection compare to placebo cream when needle touched the skin